Pengaruh Harga Saham, Volume Perdagangan dan Varian Return terhadap Bid Ask Spread pada Perusahaan yang Melakukan Stock Split pada Perusahaan yang Terdaftar di BURSA EFEK INDONESIA (BEI) - Rasyid, Rosyeni; Fitra, Halkadri; Wahyuni, Nina (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2016)
The purpose of this research is to analyze the influence of stock price, trade volume and variants return to the bid ask spread on companies doing stock split on listed on the Indonesian Stock Exchange (BEI) in 2011-2014. This type of research is the study causative. The population of this research is all companies doing stock split of the 36 companies. The sampling technique menggunakaan purposive sampling techniques in order to obtain a total sample of 17Â companies. This type of data is secondary data, and ranks the data panel. The analysis technique used is multiple regression analysis. For testing the hypothesis using statistical t-test with Î± level of 0.05. The results of this study indicate that: (1) The stock price has positive and not significant to the bid ask spread in companies that conduct a stock split, (2) the volume of stock trading positive and significant impact on the bid ask spread in companies that conduct a stock split,and(3) return variance positive and significant effect on the bid ask spread on companies doingÂ stocksplit.